2015
DOI: 10.5897/ajar2015.9513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of traditional genotypes of barley (Hordeum vulgare L.) in Algeria by pheno-morphological and agronomic traits

Abstract: Barley ranks third after durum and bread wheat grain production in Algeria. In this study, genetic diversity of twenty nine traditional genotypes of barley was assessed using twenty seven phenomorphological and agronomic traits in presence of four controls. Very high significant differences were found between genotypes for all quantitative characters statistically analyzed, indicating existence of a great variability within the germplasm. Some traditional genotypes differed from all controls by their better me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It is also a fodder crop that can be exploited as hay or grazing to rehabilitate Tunisian degraded rangelands for development in arid and semiarid areas. Several studies have reported morphological characterization to determine the genetic diversity in cultivated crops (Hadado et al, 2009;Abebe et al, 2010;Matoso et al, 2015;Rahal-Bouziane et al, 2015) and wild plants (Shakhatreh et al, 2010;Ruisi et al, 2011;Benor et al, 2012;Neji et al, 2014). The analysis of the genetic diversity is important for breeding purposes, especially to identify genes or genomic regions involved in environmental adaptations which contributes in showing high diversity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a fodder crop that can be exploited as hay or grazing to rehabilitate Tunisian degraded rangelands for development in arid and semiarid areas. Several studies have reported morphological characterization to determine the genetic diversity in cultivated crops (Hadado et al, 2009;Abebe et al, 2010;Matoso et al, 2015;Rahal-Bouziane et al, 2015) and wild plants (Shakhatreh et al, 2010;Ruisi et al, 2011;Benor et al, 2012;Neji et al, 2014). The analysis of the genetic diversity is important for breeding purposes, especially to identify genes or genomic regions involved in environmental adaptations which contributes in showing high diversity.…”
mentioning
confidence: 99%
“…Morphological characterization of plant species is mainly used to initiate a thorough investigation of genetic diversity in germplasm collections that contributes valuable information for breeding programs and conservation strategies of the concerned taxa (Benor et al, 2012). Several studies have reported morphological characterization to determine the genetic diversity in cultivated crops (Hadado et al, 2009;Abebe et al, 2010;Matoso et al, 2015;Rahal-Bouziane et al, 2015) and wild plants (Shakhatreh et al, 2010;Ruisi et al, 2011;Benor et al, 2012;Neji et al, 2014).…”
mentioning
confidence: 99%
“…There are many studies aimed at evaluating the genetic diversity of barley based on both molecular and genetic levels and agro-morphological traits (Taibi et al, 2019;Kumar et al, 2020;Brbaklić et al, 2021). For example, only in recent years were results published of assessment of barley genetic diversity in Algeria (Rahal-Bouziane et al, 2015), Oman (Al Lawati et al, 2021), Tunisia (Marzougui et al, 2020), Tibet (Li et al, 2020), Jordan (Al-Abdallat et al, 2017), Pakistan , Iraq (Lateef et al, 2021), Kazakhstan (Almerekova et al, 2021), Brasil (Monteiro et al, 2020, India (Kaur, 2022), Ethiopia (Jalata et al, 2020;Gadissa et al, 2021;Angassa & Mohammed, 2022;Teklemariam et al, 2022), Chinа (Memon et al, 2021), Palestine (Shtaya & Abdallah, 2021). Thus, it should be mentioned that even in the era of modern molecular technologies, studying genetic diversity by phenotypic traits has not lost its value.…”
Section: Discussionmentioning
confidence: 99%
“…In our set of genotypes, we detected a positive and significant correlation between days to heading, height, days to maturity and number of spikes per area, while days to heading correlated negatively with the number of grains per spike. Numbers of grain per spike has been suggested as proxy for 1000-grain weight (Al-tabbal and Al-Fraihat, 2011), but findings where there is a high, but negative correlation, challenge this suggestion (Rahal-Bouziane et al ., 2015). In congruence with the findings on other barley landraces (Setotaw et al ., 2010; Drikvand et al ., 2012), we observe that parameters related to the extent (plant height) or duration (days to heading) of the vegetative phase are the main drivers of phenotypic variability.…”
Section: Discussionmentioning
confidence: 99%